Real‐life challenges using personalized prognostic scoring systems in acute myeloid leukemia. (16th November 2022) - Calleja, Anne; Loschi, Michael; Bailly, Laurent; Morisot, Adeline; Marceau, Alice; Mannone, Lionel; Robert, Guillaume; Auberger, Patrick; Preudhomme, Claude; Raynaud, Sophie; Subtil, Fabien; Sujobert, Pierre; et al.
Abstract: Personalized medicine is a challenge for patients with acute myeloid leukemia (AML). The identification of several genetic mutations in several AML trials led to the creation of a personalized prognostic scoring algorithm known as the Knowledge Bank (KB). In this study, we assessed the prognostic value of this algorithm on a cohort of 167 real life AML patients. We compared KB predicted outcomes to real‐life outcomes. For patients younger than 60‐year‐old, OS was similar in favorable and intermediate ELN risk category. However, KB algorithm failed to predict OS for younger patients in the adverse ELN risk category and for patients older than 60 years old in the favorable ELN risk category. These discrepancies may be explained by the emergence of several new therapeutic options as well as the improvement of allogeneic stem cell transplantation (aHSCT) outcomes and supportive cares. Personalized medicine is a major challenge and predictions models are powerful tools to predict patient's outcome. However, the addition of new therapeutic options in the field of AML requires a prospective validation of these scoring systems to include recent therapeutic innovations.